Propuesta de mecanismos de prevención de riesgos laborales para la empresa pública municipal del Camal de Quevedo - Casanova Párraga, Ronnie Fabian (2017)
This research was carried out in the Municipal Public Company of the Camal of Quevedo and its main objective is the structuring mechanisms of prevention of occupational risks. Initially, the model matrix contained in the Colombian Technical Guide GTC 45 was used, this is a fundamental tool for the development of this research because it involves phases that involve criteria that allowed the technical identification of hazards, risk assessment and the establishment of intervention controls. As a result, the risk factor prevalence was: biomechanical, for which quantitative methods were applied for its evaluation, which were OWAS, RULA and the NIOSH equation; Physical, here it is necessary to know the levels of noise and labor illumination by calibrated measuring equipment and then be evaluated with national standards; Biological, in which by the nature of the process it is essential to maintain a permanent control, elaborating a cleaning and disinfection program. The information obtained served as a reference to conclude that the prevalence of the aforementioned risks represents a degree not acceptable to the health of the workers and that actions need to be taken, for which mechanisms were presented to reduce the gap that causes labor accidents.